When given a value of the variable, we replace each instance of the variable in the problem with that number. In this case, the expression becomes:
![\frac{3^2 + 3}{3 - 1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%5E2%20%2B%203%7D%7B3%20-%201%7D%20%20)
After this, we merely need to simplify the answer.
![\frac{9 + 3}{3 - 1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B9%20%2B%203%7D%7B3%20-%201%7D%20%20)
![\frac{12}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B12%7D%7B2%7D%20%20)
Simplifying 12/2 gives us the answer 6.
Answer:
His answer was wrong the answer should be 8.5 .
Step-by-step explanation:
3.8+4.7=8.5
X = Lilys weight
x + 34 = Arthurs weight
4x - 180 = combined weight
x + x + 34 = 4x = 180
2x + 34 = 4x - 180
-2x -2x
_________________
34 = 2x -180
+180 + 180
_______________
214 = 2x
107 = x which is Lily's weight
141 = x + 34 which is Arthur's weight
The total weight is 248
which is the answer that you get when you do 4(107) = 180 or
428 -180 = 248